School Experience in Facing Bantul Earthquakes Disaster Response: A Qualitative Study - Dhesi Ari Astuti; Dwi Sulisworo; Nurul Kurniati; Ika Maryani; Nursani A. Haris; Siti Fatimah (Journal of Public Health Sciences, 2025)
Earthquakes can significantly affect children's development both physically and psychologically. School experience in disaster management becomes one of the foundations for formulating needs and policies in earthquakes disaster mitigation within the school environment. This study aimed to capture the experience of schools in Bantul, Yogyakarta, in dealing with earthquakes events. Using a qualitative approach, data were collected through in-depth interviews and analyzed thematically to identify codes and themes emerging from the data, related to school-based disaster management. Analysis yielded nine major categories describing how schools prepare for, respond to, and recover from earthquakes. The findings highlight the critical role of disaster education and preparedness within school settings and reveal the need for clear procedures supporting children’s physical and psychological recovery after an earthquake. These insights underscore the importance of cross-sector collaboration and policy development to strengthen school-based disaster mitigation and post-earthquake recovery programs.